2009
DOI: 10.1590/s0100-40422009000400021
|View full text |Cite
|
Sign up to set email alerts
|

Interesterificação química de óleo de soja e óleo de soja totalmente hidrogenado: influência do tempo de reação

Abstract: Recebido em 3/6/08; aceito em 11/11/08; publicado na web em 26/2/09ChEmiCAl iNTERESTERiFiCATioN oF SoyBEAN oil AND FUlly hyDRogENATED SoyBEAN oil: iNFlUENCE oF ThE REACTioN TimE. Chemical interesterification is an important alternative to produce zero trans fats. in practice, however, excessive reaction times are used to ensure complete randomization. This work evaluated the influence of the reaction time on the interesterification of soybean oil/fully hydrogenated soybean oil blend, carried out in the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
2
9
0
2
Order By: Relevance
“…For example, Ribeiro et al (2009) reported 0.03% FFA for refined soybean oil. The peroxide index is related to the oil oxidative state and not to its characterization itself.…”
Section: Physicochemical and Thermophysical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ribeiro et al (2009) reported 0.03% FFA for refined soybean oil. The peroxide index is related to the oil oxidative state and not to its characterization itself.…”
Section: Physicochemical and Thermophysical Analysesmentioning
confidence: 99%
“…Buriti oil is an important source of energy and vitamins and has some similarities to palm oil, such as its reddish-yellow color and its flavor (Pardauil et al, 2017;Pesce et al, 2009). However, buriti oil presents a high concentration of monounsaturated fatty acids, with values higher than those found in olive oil or in Brazil nuts, which are foods known for their oil with high nutritional quality due to the monounsaturated fatty acid properties of reducing blood total and LDL-cholesterol (França et al, 1999;Silva et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fats and oils used in chemical interesterification must have low acidity, once the free fatty acids, as well as water and peroxide act as catalyst poison of sodium methoxide (RIBEIRO et al, 2009b). The peroxide values and free fatty acid contents of the native and blended oils were monitored before and after chemical interesterification.…”
Section: Oilsmentioning
confidence: 99%
“…Before the trials were done white curves to assess the baseline equipment. Curves were processed by the software Pyris, melting and crystallization curves are analyzed for the onset (Tonset °C) and endset (Tendset °C) of melting and crystallization, melting and crystallization peak temperatures (Tpf and Tpc °C) and melting and crystallization enthalpies (∆Hf and ∆Hc J/g) (RIBEIRO et al, 2009b).…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
See 1 more Smart Citation